Platelets and Regulatory T Cells May Induce a Type 2 Immunity That Is Conducive to the Progression and Fibrogenesis of Endometriosis - Xiao, Fengyi; Liu, Xishi; Guo, Sun-Wei (Frontiers in Immunology, 2020)
Endometriosis is a hormonal disease, as well as a chronic inflammatory disease. While various immune cells are documented to be involved in endometriosis, there is a lack of a bigger picture on how these cells are coordinated to work concertedly. Since endometriotic lesions experience cyclical bleeding, they are fundamentally wounds that undergo repeated tissue injury and repair (ReTIAR). In this study, we attempted to characterize the role of platelets and regulatory T cells (Tregs) in modulating the lesional immune microenvironment and its subsequent effects on lesional progression and fibrogenesis. Through two mouse experiments, we show that, by disrupting predominantly a type 2 immune response in lesional microenvironment, both platelets and Tregs depletion decelerated lesional progression and fibrogenesis, likely through the suppression of the TGF-β1/Smad3 and PDGFR-β/PI3K/Akt signaling pathways. In particular, platelet depletion resulted in significantly reduced lesional expression of thymic stromal lymphopoietin (TSLP), leading to reduced aggregation of macrophages and alternatively activated (M2) macrophages, and of Tregs, T helper 2 (Th2), and Th17 cells but increased aggregation of Th1 cells, in lesions, which, in turn, yields retarded fibrogenesis. Similarly, Tregs depletion resulted in suppression of platelet aggregation, and reduced aggregation of M2 macrophages, Th2, and Th17 cells but increased aggregation of Th1 cells, in lesions. Thus, both platelet and Tregs depletion decelerated lesional progression and fibrogenesis by disrupting predominantly a type 2 immunity in lesional microenvironment. Taken together, this suggests both platelets and Tregs may induce a type 2 immunity in lesional microenvironment that is conducive to lesional progression and fibrogenesis.